Conceptualisation and Operationalisation of the Personal Brand V.A.L.U.E. Career Development Tool - Sylvester, Ray; Donald, William E. (GILE Journal of Skills Development, 2024)
The purpose of our manuscript is to conceptualise and operationalise the Personal Brand V.A.L.U.E. Career Development Tool. The V.A.L.U.E. acronym stands for Vision, Ability, Love, Understanding, and Ecosystem. The paper adopts a case study design based on qualitative insights via an in-depth and semi-structured interview with an individual who has used the Personal Brand V.A.L.U.E. Career Development Tool over five years, initially in their final year of university (2018-2019) and subsequently as a graduate in the labour market (2019-2023). The lived experience provided through the case study provides insights into the operationalisation of the Personal Brand V.A.L.U.E. Career Development Tool for (i) preparing and navigating the university-to-work transition, (ii) navigating an unplanned career transition, and (iii) navigating a planned career transition. The theoretical contribution comes from conceptualising the Personal Brand V.A.L.U.E. Career Development Tool. The practical contribution comes from offering implications for (a) students and universities and (b) workers and organisations to operationalise the tool. A future research agenda is also presented.